IN SILICO STUDY OF YODIUM LEAF (JATROPHA MULTIFIDA LINN) ACTIVE COMPOUND AS ANTIBIOTIC FOR DIABETIC WOUNDS - HOLIK, HOLIS A.; RIFASTA, MUHAMMAD I.; MURDAYA, NIKY; SAGITASA, SALSA (International Journal of Applied Pharmaceutics, 2022)
Objective: In this study, an in silico test of 13 active compounds of leaf Jatropha multifida Linn. was carried out against the gyrase receptor (PDB ID: 2XCT). Methods: The methods include molecular docking, ADMET prediction, and a review of Lipinski's Rule of Five. Results: Molecular docking simulation results obtained three test compounds with free energy of binding (∆G) and inhibition constants (Ki) at active site A, which are lower than the comparison compound, ciprofloxacin (∆G-5.41 kcal/mol). The three compounds are C2 (multidione), C5 (citlalitrione), and C6 (cleomiscosin A) which have ΔG of-6.00,-6.90, and-5.56 kcal/mol. Based on ADMET prediction, compound C5 has better pharmacokinetics, pharmacodynamics, and toxic activities compared to ciprofloxacin. Conclusion: Therefore, C5 is the best active compound from J. multifida, which can be used as a candidate for new antibiotics in the treatment of diabetic wounds.